2001
DOI: 10.1002/1097-0142(20010301)91:5<940::aid-cncr1083>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction paclitaxel and carboplatin for patients with head and neck carcinoma

Abstract: Induction paclitaxel and carboplatin was well tolerated. The response rate was encouraging considering most patients were Stage IV. Chemotherapy response identified a group with improved prognosis. Organ preservation was possible at all anatomic sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
(13 reference statements)
0
15
0
1
Order By: Relevance
“…Dunphy et al, 9 Stathopoulos et al, 14 and Fountzilas et al 8 reported response rates of 54%, 39%, and 23%, respectively. Of note, however, the report by Dunphy et al 9 included patients with newly diagnosed, previously untreated disease and reported a 60% response rate for patients with nasopharyngeal carcinoma, a highly chemotherapy-sensitive malignancy, but only a 23% response rate for other primary SCCHN.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Dunphy et al, 9 Stathopoulos et al, 14 and Fountzilas et al 8 reported response rates of 54%, 39%, and 23%, respectively. Of note, however, the report by Dunphy et al 9 included patients with newly diagnosed, previously untreated disease and reported a 60% response rate for patients with nasopharyngeal carcinoma, a highly chemotherapy-sensitive malignancy, but only a 23% response rate for other primary SCCHN.…”
Section: Discussionmentioning
confidence: 98%
“…Three patients in this group suffered treatment-related deaths due to sepsis as a direct result of febrile neutropenia and likely bleeding due to thrombocytopenia. In another Phase I and II studies that have used carboplatin and paclitaxel, Dunphy et al 9 reported a 67% incidence of neutropenia and 1 patient with death due to neutropenic sepsis. Stathopoulos et al 14 reported 17% incidence of neutropenic fevers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently taxol combined with a platinum agent is considered to be the one of the most promising adjuvant chemotherapy regimens in advanced ovarian cancer [2]. It has also been reported to be effective against various carcinomas including non-small cell carcinoma of the lung [3], breast [4] and head and neck cancer [5] in adult population as well as the pediatric age group. Like the other antineoplastic agents, taxol also has many side effects of which neutropenia and peripheral neuropathy are the major dose-limiting ones [6].…”
Section: Introductionmentioning
confidence: 99%